MODALITY AND NEW ARENA: NU AND MUHAMMADIYAH IN THE LOCAL ELECTION GUNUNG KIDUL REGENCY - Harirah MS, Zulfa (CosmoGov: Jurnal Ilmu Pemerintahan, 2021)
The relation of NU - Muhammadiyah in the history of modern Indonesia is indeed very interesting. Throughout the course of this largest Islamic organization is often colored by coordination, competition, and even confrontation. Reflecting on the Regent's election contestation in Gunung Kidul Regency, Yogyakarta became a real "battleground" for Muhammadiyah and NU organizations to show its existence. The stretching of the relationship between NU and Muhammadiyah is strongly influenced by the existence of their political machines, namely PKB and PAN. Therefore, this study will focus to identify the capital owned by NU and Muhammadiyah and to track the strategies undertaken between NU and Muhammadiyah in utilizing this capital in the simultaneous post-conflict local election as a structure of opportunities. To answer that questions above, this research was carried out through a case study method and used the modality framework as stated by Pierre Bourdieu. The results of this study indicate that there was no increase in exchange between CSOs and candidates in the election of the Regent in the Regency. Gunung Kidul. The post-conflict local election only gives a new field to habitus that has been settled, because the exchange that occurs is a manifestation of relations that have been institutionalized before.gb777